Review and Comment on the Relationship between Primo Vascular System and Meridians. (14th May 2013) - Cai, Ding-Jun; Chen, Ji; Zhuang, Yi; Liu, Mai-Lan; Liang, Fan-Rong
Abstract : This paper aims to summarize the recent progress of researches on the primo vascular system (PVS) and to analyze characteristics between PVS and traditional Chinese meridians. With the distribution, position features, identification and origin of PVS, and its function related to meridians elaborated on, we propose that there is still a lack of enough evidence to support the correlation between PVS and traditional Chinese meridians.